PEDAGOGICAL AND PSYCHOLOGICAL FACTORS OF ADDICTION TO MOBILE COMMUNICATIONS IN STUDENTS (Universal International Scientific Journal, 2026)
This article analyzes the social and psychological aspects of mobile phone addiction among students. The role of mobile technologies in everyday life, their impact on the adaptation of young people to the social environment, as well as the formation of addiction through psychological factors - anxiety, low self-esteem, need for attention - are highlighted. At the end of the article, ways to reduce the problem are recommended - digital hygiene, increasing social activity, and psychological training.
Keywords: mobile addiction; student youth; psychological factors4